In ovo injection of organic zinc effects on hatching rate of broiler breeder hen eggs and productivity of broilers - Ghane-Khoshkebijari, F; Seidavi, A; Bouyeh, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to investigate the effect of in ovo injection of organic zinc on the characteristics of broiler chickens and the performance of broiler chickens A total of 320 eggs from Ross 308 strain with an average weight of 65 grams were randomly divided into four groups, negative control (no injection), positive control (in ovo injection of 0.272 ml of normal saline solution) and two experimental groups, eggs in the first received in ovo injection of 0.272 mg of organic zinc whereas in the second the eggs were injected with 0.544 mg of the same organic zinc. The injection was done in the amniotic sac on the 10th day of incubation. The effect of injection on hatching traits and then on functional traits, blood parameters, immune response, carcass characteristics and cecal microbial population of resulting broilers were measured. The results showed that the percentage of hatched broiler chickens in the zinc-treated groups was significantly lower compared to the two control groups. However, the intraocular injection of zinc caused a significant increase in the final weight gain of the birds and their feed consumption. Blood parameters were also affected in experimental treatments and blood glucose increased and blood triglyceride, cholesterol and lipoproteins decreased compared to negative and positive control (P<0.01). On the other hand, no statistically significant difference was observed in the immune response, microbial population and carcass characteristics among the experimental groups. In conclusion, the intra egg injection of organic zinc can show favorable results in the performance indicators of broiler chickens, although it had no effect on the immune response and microbial population.